i would like the following equation in the form z=f(v,w,x,y,const)

$\displaystyle

const=w-(x-yz)^2/(v+y) + yz^2

$

Is this possible and if so how?

Printable View

- Jul 21st 2009, 03:15 AMdeanj2k1just rearranging an equation, is it possible?
i would like the following equation in the form z=f(v,w,x,y,const)

$\displaystyle

const=w-(x-yz)^2/(v+y) + yz^2

$

Is this possible and if so how? - Jul 21st 2009, 07:12 AMbananaxxx
Yes, do you know how to complete the square?

Completing the square - Wikipedia, the free encyclopedia